Efficacy of tezepelumab in patients with severe asthma and persistent airflow obstruction - Elliot Israel; Mario Castro; Christopher S. Ambrose; Jean-Pierre Llanos; Nestor A. Molfino; Nicole L. Martin; Sandhia S. Ponnarambil; Neil Martin (ERJ Open Research)
Background Persistent airflow obstruction (PAO) in patients with asthma can be difficult to treat. Tezepelumab blocks thymic stromal lymphopoietin, an epithelial cytokine implicated in asthma pathogenesis. This analysis evaluated the efficacy of tezepelumab in patients with severe, uncontrolled asthma and PAO. Methods PATHWAY (phase 2b) and NAVIGATOR (phase 3) were multicentre, randomised, double-blind, placebo-controlled studies. This post hoc analysis included PATHWAY and NAVIGATOR patients who received tezepelumab 210 mg or placebo every 4 weeks for 52 weeks. Change from baseline to week 52 in pre-bronchodilator forced expiratory volume in 1 s (FEV1) and the annualised asthma exacerbation rate (AAER) over 52 weeks were assessed in patients with and without PAO (post-bronchodilator FEV1/forced vital capacity ratio <0.7) at baseline. Results Of the 1334 included patients, 782 (58.6%) had PAO at baseline. At week 52, greater improvements in pre-bronchodilator FEV1 from baseline were observed in tezepelumab versus placebo recipients with PAO (least-squares (LS) mean 0.24 versus 0.07 L; difference 0.17 L, 95% confidence interval (CI): 0.11–0.23) and without PAO (LS mean 0.20 versus 0.12 L; difference 0.08 L, 95% CI: 0.01–0.15). Tezepelumab reduced the AAER versus placebo by 61% (95% CI: 51–69) and 56% (95% CI: 42–67) in patients with and without PAO, respectively. For patients with PAO at baseline, the proportion without PAO at week 52 was higher with tezepelumab (12.1%) than placebo (6.6%) (odds ratio 1.96, 95% CI: 1.30–2.94). Conclusion Tezepelumab improved lung function and reduced exacerbations versus placebo in patients with severe, uncontrolled asthma with and without PAO.